Digital Monitoring System for Field Work Practice in Vocational Schools - Asri; Ming-Chung Chang; Akbar Iskandar; Maria Yertas (Yayasan Cendekiawan Digital Indonesia, 2026)
The implementation of Field Work Practice (PKL) in vocational schools still faces administrative and monitoring challenges due to reliance on manual reporting systems. These limitations affect reporting efficiency, transparency, and teachers' ability to monitor student activities in real time. This community service activity aimed to implement and assist the use of a web-based PKL monitoring system at SMK Nasional Makassar to support digital monitoring, reporting, and evaluation of PKL activities. The implementation process included needs analysis, system design, implementation, user socialization, mentoring, and evaluation using the Waterfall approach. Data were collected through observation, interviews, and literature review. System evaluation was conducted through Black Box Testing and User Acceptance Testing (UAT). The Black Box Testing results showed that all main system functions operated properly in accordance with user requirements. Furthermore, the UAT results showed a feasibility percentage of 88.5%, indicating that the system was categorized as “Very Feasible.” The implementation of the system improved the effectiveness of real-time monitoring, digital reporting, data management, and administrative efficiency of PKL activities in vocational schools. The findings demonstrate that the web-based monitoring system can effectively support digital transformation in vocational education management.